Effects of Massage Therapy on Anxiety in Heart Disease Patients: A Systematic Review - Beti Kristinawati; Bintang Viga Handika; Ardhu Rizkiawan; Nyofan Wahyu Mardana; Nove Wiand Dwi Wijayanti (Nurse Media: Journal of Nursing, 2025)
Background: Patients with heart disease often experience anxiety as a response to physiological changes, and massage therapy is one of the alternative treatments available to alleviate this condition. Although the benefits of massage therapy in reducing anxiety are well recognized, there is a lack of focused research evaluating its specific effects on individuals with heart disease.